FUNGSI BERNILAI VEKTOR - -, Suwandi (Universitas Pasir Pengaraian, 2012)
The definition of function f is a role that relates between x of one items and single value f(x) of others items. It can be a real scalar and vector. Scalar function is coming from real counts items and a couple items or a result of a real count items.However, vector is coming from a real count items and the result vector items. They are not so different; vector has direction and value while the real counts only have value. Vector will be analyzed is to prove vector and differential theorem function used to vector in R2.